2023
DOI: 10.1111/pbi.14006
|View full text |Cite
|
Sign up to set email alerts
|

Host‐ and virus‐induced gene silencing of HOG1‐MAPK cascade genes in Rhizophagus irregularis inhibit arbuscule development and reduce resistance of plants to drought stress

Abstract: Summary Arbuscular mycorrhizal (AM) fungi can form beneficial associations with the most terrestrial vascular plant species. AM fungi not only facilitate plant nutrient acquisition but also enhance plant tolerance to various environmental stresses such as drought stress. However, the molecular mechanisms by which AM fungal mitogen‐activated protein kinase (MAPK) cascades mediate the host adaptation to drought stimulus remains to be investigated. Recently, many studies have shown that virus‐induced gene silenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 90 publications
0
23
0
Order By: Relevance
“…The Ri14-3-3 protein in R. irregularis is essential for arbuscule formation ( 71 ). We also analyzed the expression levels of RiAQP1 , RiAQP2 , RiTPS1 , RiTPS2 , RiNTH1 , and Ri14-3-3 from R. irregularis in mycorrhizal E. grandis , which were identified previously by Wang et al ( 52 ). We observed that the transcriptional levels of RiAQP1 , RiAQP2 , RiTPS1 , RiTPS2 , RiNTH1 , and Ri14-3-3 were increased significantly under ED conditions ( Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The Ri14-3-3 protein in R. irregularis is essential for arbuscule formation ( 71 ). We also analyzed the expression levels of RiAQP1 , RiAQP2 , RiTPS1 , RiTPS2 , RiNTH1 , and Ri14-3-3 from R. irregularis in mycorrhizal E. grandis , which were identified previously by Wang et al ( 52 ). We observed that the transcriptional levels of RiAQP1 , RiAQP2 , RiTPS1 , RiTPS2 , RiNTH1 , and Ri14-3-3 were increased significantly under ED conditions ( Fig.…”
Section: Discussionmentioning
confidence: 89%
“…According to the released genome of E. grandis ( 48 ), plasma-membrane-intrinsic proteins ( EgPIP1 and EgPIP2 ) and tonoplast-intrinsic proteins ( EgTIP1 and EgTIP2 ) were identified using related PIP and TIP genes in other plants ( 28 , 29 ). We also identified aquaporin ( RiAQP1 , - 2 , and - 3 ), trehalose-6-phosphate synthase (TPS) ( RiTPS1 and - 2 ), neutral trehalase (NTH) ( RiNTH1 ), and Ri14-3-3 genes in R. irregularis according to a previous study ( 52 ). There were no significant differences in the expression levels between AM and NM plants under WW conditions.…”
Section: Resultsmentioning
confidence: 99%
“…STRE is a stress response element (core consensus: AGGGG or CCCCT), which can be activated by various stress factors (Ruis & Schüller, 1995;Siderius & Mager, 1997). It has been reported that the mitogen-activated protein kinase (MAPK) cascade participates in the AM fungal and host plant symbionts in responses to drought stress (Liu et al, 2015;Huang et al, 2020;Wang et al, 2023). Very recently, Wang et al (2023) identified three Hog1-MAPK cascade genes from R. irregularis, RiSte11, RiPbs2, and RiHog1, the higher expression of three Hog1-MAPK genes increased the resistance of mycorrhizal plants to drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the mitogen-activated protein kinase (MAPK) cascade participates in the AM fungal and host plant symbionts in responses to drought stress (Liu et al, 2015;Huang et al, 2020;Wang et al, 2023). Very recently, Wang et al (2023) identified three Hog1-MAPK cascade genes from R. irregularis, RiSte11, RiPbs2, and RiHog1, the higher expression of three Hog1-MAPK genes increased the resistance of mycorrhizal plants to drought stress. It is a proven fact that the yeast protein kinase Hog1 (high osmolarity glycerol 1) regulates many target genes through the transcriptional activators Msn2/4, Hot1, and Sko1 (Capaldi et al, 2008;Azad et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation